Examining the Compatibility of Students in Distributed Pair Programming - Satratzemi, Maya; Tsompanoudi, Despina; Xinogalos, Stelios; Karamitopoulos, Leonidas (Proceedings of the ... European conference on e-learning (Online), 2019)
Pair Programming (PP) has a long history both in the software industry and education. More recently, specially designed environments have made the application of Distributed Pair Programming (DPP) possible, which enables two programmers to work remotely. Through these collaborative activities, students produce better programs, improve their performance and programming skills, and increase their self-confidence. Student attitudes towards Distributed Pair Programming and the factors that affect them, remain largely unexplored, while some of the existing studies have yielded mixed results. One important aspect is to understand the underlying factors that contribute to a successful pairing formation, i.e., factors that make pairs very compatible. This paper focuses on the examination of possible factors which we felt had the potential to affect the compatibility of student pairs who worked remotely. The present study was conducted in the context of a 3rd semester undergraduate "Object-Oriented Programming" course. The OOP concepts were approached through hands-on exercises completed in the lab sessions. Students carried out projects in pairs using the educational DPP system SCEPPSys. The analyzed data were collected from a pre and post questionnaire distributed to students before and after the end of the course, respectively. Pair Compatibility was examined in relation to pair perceived skill level, pair actual skill level, and pair programming self-esteem. Besides this, we examined if students' perceptions on the factors they believe hinder collaboration differ on the basis of their compatibility. The findings indicated that the compatibility rating differed significantly based on the partner's perceived technical competence. Also, students that rated their partners as very compatible had more similar actual skill level with their partners than those students who rated their partners as notcompatible or satisfactorily compatible. We did not find any relationship between compatibility and pair programming selfesteem. Lastly, very compatible pairs rated the following three factors as hindering collaboration less negatively than notcompatible or satisfactorily compatible pairs: a) coordination problems (collaboration time), b) unreliable partner, and c) lack of partner knowledge.